Fiscal consolidation, public debt, and growth in Jordan: Evidence from public and municipal finance indicators - Khaled Bataineh (Public and Municipal Finance, 2026)
Type of the article: Research ArticleAbstractThe purpose of this study is to examine whether fiscal balance, revenue mobilization, and real economic growth are associated with annual changes in Jordan’s public debt-to-GDP ratio during 2014–2024 and to interpret the implications for public and municipal finance. The study uses annual macro-fiscal data compiled from the IMF Regional Economic Outlook series hosted by FRED, World Bank indicators, the Central Bank of Jordan, and Ministry of Finance reports. It applies descriptive analysis, correlation analysis, and parsimonious ordinary least squares specifications, with all coefficients, p-values, diagnostic tests, and robustness checks interpreted cautiously because the usable regression sample after first differencing is very small. The results show that the public-debt ratio increased from 78.0% of GDP in 2019 to 88.0% in 2020 and remained above 90% during 2021–2024. Revenue excluding grants recovered from 20.1% of GDP in 2020 to 24.1% in 2024, but this recovery did not restore the debt ratio to its pre-pandemic path. In a short annual sample, the baseline regression suggests that fiscal balance is negatively associated with annual debt changes, while real GDP growth has the expected negative sign but weaker statistical significance. These results are indicative rather than causal and should be read together with debt-dynamics theory and Jordan’s fiscal policy context. The findings are consistent with a cautious, growth-friendly consolidation approach, interpreted as an indicative policy implication rather than a direct causal estimate, that strengthens revenue administration, protects productive capital expenditure, manages utility-related guarantees, and improves municipal finance transparency.